2015
DOI: 10.1002/clc.22385
|View full text |Cite
|
Sign up to set email alerts
|

Commonly Consumed Beverages in Daily Life: Do They Cause Atrial Fibrillation?

Abstract: Atrial fibrillation (AF) is the most prevalent cardiac arrhythmia in the United States and worldwide. Caffeine, alcohol, and, more recently, energy drinks are the most commonly consumed beverages in daily living, especially by young individuals. Several questions have been raised about the implications of caffeine, alcohol, and energy drinks in cardiovascular health, especially in triggering AF. This review focuses on the role of these commonly consumed beverages as a cause of AF, with special emphasis of pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 58 publications
(95 reference statements)
0
14
0
Order By: Relevance
“…Other ingredients in EDs including "energy blends" and herbs could potentially trigger arrhythmias as well [15]. Atrial fibrillation has been observed following acute ingestion of EDs in young adults [50]. It is unknown whether these individuals had a genetic predisposition towards arrhythmia or if ingredients in the EDs triggered the events [50].…”
Section: Supraventricular Arrhythmiamentioning
confidence: 99%
See 1 more Smart Citation
“…Other ingredients in EDs including "energy blends" and herbs could potentially trigger arrhythmias as well [15]. Atrial fibrillation has been observed following acute ingestion of EDs in young adults [50]. It is unknown whether these individuals had a genetic predisposition towards arrhythmia or if ingredients in the EDs triggered the events [50].…”
Section: Supraventricular Arrhythmiamentioning
confidence: 99%
“…Atrial fibrillation has been observed following acute ingestion of EDs in young adults [50]. It is unknown whether these individuals had a genetic predisposition towards arrhythmia or if ingredients in the EDs triggered the events [50]. It is important to note that atrial fibrillation is extremely rare in the pediatric population and it almost always occurs in association with structural heart disease [51].…”
Section: Supraventricular Arrhythmiamentioning
confidence: 99%
“…Rather, the physician advised, not against cold drinks, but against coffee, although this was not the precipitant of the patient’s headache or dysrhythmia. Though it might be prudent for a patient with paroxysmal AF to limit caffeine ingestion, the relationship between coffee ingestion and incident AF has been called into question by a number of studies [ 34 ]. Just as in our case report, none of the five emergency physicians caring for the patients with cold-induced AF from our Pharm CAFÉ Study reported advising their patients to avoid re-exposure to ice-cold drinks.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological evidence over the last decade has identified that metabolic syndrome, prehypertension, obesity, obstructive sleep apnea, exercise, and dietary intake of stimulants are major risk factors for AF [4,6]. However, only a small proportion of exposed individuals eventually developed AF, suggesting that a strong genetic component might be a risk factor contributing to the susceptibility of AF.…”
Section: Introductionmentioning
confidence: 99%